Anomalous electrical magnetochiral effect by chiral spin-cluster scattering - Hiroaki Ishizuka (Nature Portfolio, 2020)
The microscopic mechanism for nonreciprocity of electron transport in bulk materials remains less well understood. Here, the authors show that asymmetric electron scattering by two-spin clusters induce nonreciprocal current (electric current proportional to the square of the electric field) in magnetic metals.